2015
DOI: 10.5935/abc.20150150
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Factors and Adverse Perinatal Outcomes in Women with Preeclampsia in Maceió, Alagoas

Abstract: BackgroundPreeclampsia has been associated with several risk factors and events. However, it still deserves further investigation, considering the multitude of related factors that affect different populations.ObjectiveTo evaluate the maternal factors and adverse perinatal outcomes in a cohort of pregnant women with preeclampsia receiving care in the public health network of the city of Maceió.MethodsProspective cohort study carried out in 2014 in the public health network of the city with a sample of pregnant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 28 publications
(27 reference statements)
1
14
0
8
Order By: Relevance
“…Some studies indicate that the most common type of delivery, in cases of hypertensive syndromes, is emergency cesarean section. 11,17 In a study conducted in Campina Grande, PB, about 68.6% of the deliveries were delivered by caesarean section and 31.4% by vaginal route, corroborating with the data of this research. 17 However, a study conducted in a teaching hospital in the Paulista Interior showed a higher prevalence of adverse events such as postpartum hemorrhage in cesarean sections.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Some studies indicate that the most common type of delivery, in cases of hypertensive syndromes, is emergency cesarean section. 11,17 In a study conducted in Campina Grande, PB, about 68.6% of the deliveries were delivered by caesarean section and 31.4% by vaginal route, corroborating with the data of this research. 17 However, a study conducted in a teaching hospital in the Paulista Interior showed a higher prevalence of adverse events such as postpartum hemorrhage in cesarean sections.…”
Section: Discussionsupporting
confidence: 86%
“…4 Another study emphasized other complications in cesarean delivery such as infections, hypertensive peaks, longer hospitalization, hemorrhagic manifestations. 11 Regarding the way of delivery, evidence emphasizes that the cesarean route will not always be specific for high-risk pregnancies such as hypertensive syndromes. 11,[22][23] In the variable on the number of prenatal consultations, the results obtained mean that most of the pregnant women presented more than six consultations, opening space for reflections about the data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations